Gender, Space and Development: A Theoretical Perspective - Kushwaha, Neha; Singh, Jagadish (National Geographical Journal of India, 2022)
Gender is defined as a socially constructed category that carries with it expectations and responsibilities that are not biologically determined. Space is constructed out of continuous co-existence of social inter relations. Women’s space is defined as women’s access to and control over material resources (food, income and land ) and social resources (knowledge, power and prestige) within the family, in the community and society at large. Gender roles are thus seen as constructed in part through our culturally experienced bodies and the ways men and women experience their bodies becomes a part of their experience of gender and gender relations (Raju, 2001). The role of women and men in the development process has received much attention in the last few decades. This paper attempts to discuss conceptual framework of geography of gender and theoretical perspectives on Women in Development (WID), Women and Development (WAD), Gender and Development (GAD) and Gender and Space .The geography of gender explores the way space is implicated in articulated gender relationships.